Turistas - Stockwell, John; Ross, Michael Arlen (Twentieth Century Fox ; distributed in the Philippines by Viva Video, 2006)
After a terrifying bus accident maroons a diverse group of young adventure travelers in a remote Brazilian beach town, they slowly discover that the white sand beaches and lush jungles are concealing a darker, unsettling secret.